MANAGEMENT AND OUTCOME OF DIABETIC PREGNANCY - Dr. Mubashra Naz (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives: To observe the effects of management of diabetes on pregnancy outcome in terms of maternal morbidity, immediate neonatal morbidity and mortality. Study design: It was a descriptive study. Place and duration of study: Obstetrics and gynaecology Unit 2, Divisional Headquarter Hospital Punjab, Punjab Medical College, Faisalabad from January 2006 to December 2006. Methods: All patients following inclusion and exclusion criteria on the bases of history and clinical examination were selected. Patients were managed with diet, exercise and insulin therapy for a period of 2 to 7 months. Fetal surveillance was done with cardiotocography and growth scans. Delivery was planned at 38 weeks of gestation according to cervical score, previous obstetrics and complications arising in current pregnancy. Main out come measures recorded and results calculated. Results: Sample size comprised 80 gestational and 20 pre gestational diabetics. Hypertensive disorders complicated 21% pregnancies. Hydramnios and pre term labor each was present in 13% of patients. The mode of delivery was abdominal in 56% cases. Three patients suffered from shoulder dystocia. Amongst 10 prenatal deaths 3 were due to congenital malformations, 4 were unexplained still births and 3 babies died in early neonatal period due to metabolic complications like hypoglycemia, jaundice and hypocalcaemia which occurred in 33% neonates. Conclusion: Prenatal counseling for established diabetics, screening and diagnosis for all pregnant population, good control from conception till delivery, antepartum fetal surveillance and appropriate neonatal support are the key to successful outcome in diabetic pregnancy